1977
DOI: 10.3758/bf03209576
|View full text |Cite
|
Sign up to set email alerts
|

Location preference and flavor aversion reinforced by amphetamine in rats

Abstract: To associate the identical drug state with both a loeation and a flavor, rats were given intraperitoneal amphetamine injeetions and then eonfined for 20 min in one side of a shuttlebox with aecess to a flavored solution; on control trials without injections, they were confined for 20 min in the opposite side with a different flavor. In the first experiment, the rats were plaeed in the shuttlebox immediately after injections; in the second experiment, they were placed in the shuttlebox 20 min after injections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(99 citation statements)
references
References 5 publications
6
92
0
Order By: Relevance
“…Even so, it was viewed as highly paradoxical that such drugs, drugs that were readily selfadministered by rats and man [27], also evidenced aversive properties in the CTA paradigm. Indeed, in three key experiments, avoidance of the taste cue was found to be accompanied, in the exact same study, by faster running for the drug [28], more time spent in the drug-paired compartment in a conditioned place preference task [29], and avid self-administration of the drug [24]. Since this time, additional evidence has been generated to show that addictive agents have aversive properties [25, 30 , 31 ] and the aversive response to the taste cue following tastedrug pairings has been attributed to a range of factors including stimulus novelty, drug shyness (i.e., fear of novel drug or drug-induced state), fear [32], and positive conditioned suppression (i.e., where responding is suppressed by stimuli that precede the response-independent presentation of shock or food, for example) [33][34][35][36].…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 73%
“…Even so, it was viewed as highly paradoxical that such drugs, drugs that were readily selfadministered by rats and man [27], also evidenced aversive properties in the CTA paradigm. Indeed, in three key experiments, avoidance of the taste cue was found to be accompanied, in the exact same study, by faster running for the drug [28], more time spent in the drug-paired compartment in a conditioned place preference task [29], and avid self-administration of the drug [24]. Since this time, additional evidence has been generated to show that addictive agents have aversive properties [25, 30 , 31 ] and the aversive response to the taste cue following tastedrug pairings has been attributed to a range of factors including stimulus novelty, drug shyness (i.e., fear of novel drug or drug-induced state), fear [32], and positive conditioned suppression (i.e., where responding is suppressed by stimuli that precede the response-independent presentation of shock or food, for example) [33][34][35][36].…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 73%
“…In support ofthis suggestion, one study with morphine has shown that simultaneous conditioning produces a conditioned taste preference, whereas standard trace delay conditioning produces conditioned taste aversion (Lett & Grant, 1989). However, in other studies involving either simultaneous or short backward intervals with amphetamine, taste aversion was produced even though the same drug injection conditioned preference to exteroceptive stimuli presented together with the taste CS (Reicher & Holman, 1977). Thus, it does not appear that the place preference-taste aversion paradox can be explained entirely in terms ofISI differences.…”
Section: /20%mentioning
confidence: 85%
“…Specifically, many reports show that drugs that produce conditioned place preference will also induce conditioned taste aversion (e.g., Cunningham et aI., 1991;Reicher & Holman, 1977;Smith & Holman, 1987). Indeed, several studies from this laboratory have shown that the same dose ofethanol as that used here establishes a robust conditioned taste aversion in DBA/2 mice (Risinger & Cunningham, 1992b, 1995.…”
Section: /20%mentioning
confidence: 96%
See 2 more Smart Citations